Magnetic framework composites for CO2 capture - Woodliffe, John Luke (2024)
Climate change is possibly the greatest challenge currently facing mankind. Immediate action is required to prevent the most devastating effects, particularly on developing nations. This change is being driven by record levels of atmospheric CO2, largely emitted during electricity and heat production. A promising solution is post-combustion carbon capture, which can be retrofitted into existing power stations and allows for the capturing of CO2 at source, removing it from flue gas mixtures. Metal-organic frameworks (MOFs) are highly porous materials consisting of metal ions or clusters linked by organic molecules. MOFs have demonstrated excellent potential for CO2 capture applications due to their high sorption capacities and selectivities for CO2 over other gases. However, MOFs are naturally thermal insulators, making thermal regeneration (emptying the MOF after each adsorption cycle for reuse) challenging, especially on the larger scales required in industrial settings. This limitation can be overcome by forming composites of magnetic materials with the MOFs (magnetic framework composites, MFCs) enabling rapid and energy efficient thermal regeneration by magnetic induction heating.